2013
DOI: 10.3389/fpls.2013.00347
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and morphology of fine roots of sugi (Cryptomeria japonica) after 3 years of nitrogen fertilization

Abstract: Increasing nitrogen (N) deposition may affect carbon and nutrient dynamics in forest ecosystems. To better understand the effects of N deposition, we need to improve our knowledge of N effects on fine roots (roots <2 mm in diameter), as they are a key factor in carbon and nutrient dynamics. In this study, we fertilized 1 × 2 m plots in a sugi (Cryptomeria japonica) stand (336 kg ha-1 y-1) for 3 years and evaluated the responses of the fine roots to high N load. After fertilization, the concentration of NO3–N i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 40 publications
(58 reference statements)
1
26
0
2
Order By: Relevance
“…There have been reports of positive, negative, and no effect of N addition on fine root biomass. While some studies showed an increase in fine root biomass following N addition Nadelhoffer 2000;Noguchi et al 2013;Pregitzer et al 1993;Wang et al 2016), others showed that N addition and higher N availability reduced fine root production and turnover in forests (Burton et al 2000;Peng et al 2017;Tateno et al 2004;Wang et al 2012;Wurzburger and Wright 2015). Moreover, some studies even showed that N fertilization had no effect on fine root biomass or length density (Genenger et al 2003;Pregitzer et al 1995;Tingey et al 1996).…”
Section: Fine Root Morphological Traits and Biomass In Response To N mentioning
confidence: 99%
“…There have been reports of positive, negative, and no effect of N addition on fine root biomass. While some studies showed an increase in fine root biomass following N addition Nadelhoffer 2000;Noguchi et al 2013;Pregitzer et al 1993;Wang et al 2016), others showed that N addition and higher N availability reduced fine root production and turnover in forests (Burton et al 2000;Peng et al 2017;Tateno et al 2004;Wang et al 2012;Wurzburger and Wright 2015). Moreover, some studies even showed that N fertilization had no effect on fine root biomass or length density (Genenger et al 2003;Pregitzer et al 1995;Tingey et al 1996).…”
Section: Fine Root Morphological Traits and Biomass In Response To N mentioning
confidence: 99%
“…In the organic horizons of the forest floor, the middle and lower layers are enriched in water and nutrients relative to the upper litter and mineral soil layers, and this enrichment provides favorable conditions for root growth (Subke et al 2004;Sayer et al 2006;Achat et al 2008;Hodge et al 2010). There have been numerous studies on the proliferation of fine roots in mineral soils, but knowledge of fine root growth into the litter layer, especially into fresh litter, remains incomplete (Noguchi et al 2013;Liu et al 2014;Zhou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce competition and improve nutrient use efficiency, various plants in the forest community may adjust the biomass, spatial distribution, morphology, and architecture of their fine roots Ostonen et al 2007;Finér et al 2011;Noguchi et al 2013). Accurate estimates of fine root biomass and form are therefore essential for understanding forest ecosystem function (Børja et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a metaanalysis of mycorrhizal responses to nutrient fertilization indicates that mycorrhizal colonization rates were negatively related to P availability, but the response to N availability was inconsistent (Treseder 2004). Anthropogenic N deposition has doubled the input of reactive N (Galloway et al 2008) which is quantitatively and functionally the most important nutrient for plants and microbes (Noguchi et al 2013). However, as N deposition rate persistently exceeds N demand of plants and microbes, 'N saturation' may occur with a suite of negative effects, such as soil acidification, loss of soil cations, and shift from N to P limitation or further P and N colimitation (Aber et al 1989;Matson et al 1999;Braun et al 2010;Cairney 2011), all of which will influence the fine root deployment, growth, and traits associated with nutrient foraging.…”
Section: Introductionmentioning
confidence: 99%